2005
DOI: 10.1111/j.1528-1167.2005.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline in Severe Intractable Epilepsy

Abstract: Summary:Purpose: To explore the relation between seizurerelated variables and cognitive change in patients with severe intractable epilepsy.Methods: A retrospective analysis of data from 136 patients who had undergone a cognitive assessment on two occasions at an interval of ≥10 years. Cognitive measures included tests of memory and executive skills in addition to intelligence quotients (IQ). Details were available regarding seizure type and frequency in the intertest interval.Results: Cognitive decline was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 30 publications
8
125
2
3
Order By: Relevance
“…A study in 136 patients with refractory epilepsy found that "cognitive decline was severe and occurred across a wide range of cognitive functions." 16 Favorable effects on cognition have also been reported for thalamic stimulation. A case series study 17 reported 9 patients with intractable epilepsy treated with continuous anterior nucleus of the thalamus (ANT) DBS who underwent cognitive testing before implantation and more than 1 year after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…A study in 136 patients with refractory epilepsy found that "cognitive decline was severe and occurred across a wide range of cognitive functions." 16 Favorable effects on cognition have also been reported for thalamic stimulation. A case series study 17 reported 9 patients with intractable epilepsy treated with continuous anterior nucleus of the thalamus (ANT) DBS who underwent cognitive testing before implantation and more than 1 year after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…When cognitive decline, recognised as particularly rare in childhood epilepsy, does occur, it is explained by pre-existing structural brain damage 22 , the adverse effect on an immature brain of early onset seizures, especially when frequent and resistant to treatment 22,23 or the side effects of antiepileptic drugs AED 24 . These children had received virtually no AED, apart from herbal remedies, and the possible adverse affects of traditional medicine or absolute lack of treatment cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…14,49 In children with treatment-resistant epilepsy, better seizure control can result in improved developmental and cognitive outcome and quality of life. 13,18,27,28,31,54 Moreover, numerous studies found that VNS can benefit attention, cognition, behavior, mood, and quality of life independent of reduced seizure burden.…”
Section: Seizure Control and Developmentmentioning
confidence: 99%